A Passion for video: 25 stories about making, translating, sharing and using videos on farmer innovation - Bentley, Jeffery; Boa, Eric; Salm, Mundie (Technical Centre for Agricultural and Rural Cooperation, 2016)
Since 2013, Access Agriculture has been training young professionals from various organisations in six African countries to make farmer-to-farmer videos. The videos are a way of moving ideas faster, and more clearly, beyond borders. The Access Agriculture website hosts the videos by these young professionals, and by other agencies, if the videos meet Access Agriculture’s quality and style standards. Access Agriculture encourages all organisations working in developing countries to invest in translating videos available on the website into any language. Access Agriculture offers a fee-based translation service to anyone interested in using quality videos in their own farmer training programmes. The stories in this volume were gathered as part of a Writeshop held in Nairobi on 9–10 November, in the context of the Access Agriculture Week 9–13 November, 2015